Static calculation of the Vantur bridge - Maya Chanturia; Merab Mamardashvili (Interdisciplinary Science Studies, 2024)
Transport communications, including bridges, greatly determine the prosperity of the state and its development prospects. Types of modern bridges are very diverse. They can be classified in different ways. An important feature of Vantur bridges is the diversity of their construction forms. The Vantur bridge, as a dominant element of the architectural ensemble, places increased demands on architects and engineer-constructors, as a result of which Vantur bridges, compared to other system bridges, are distinguished by their construction diversity